Quantification of shedding of leaves in yerba mate and determination of associated hormonal levels - Molina, Sandra Patricia; Andrade, Andrea Mariela; Habel Bruera, Glenda Elizabet; Olinuck, Jose Angel (Studies Publicações, 2022)
In recent years, leaf shedding in the yerba mate crop has been a phenomenon of important economic incidence, the cause of which is still unknown but has been attributed to various factors. The objective of the present study was to establish a methodology to quantify leaves shedding in yerba mate and to determine whether the high leaf shedding is due to a biotic or abiotic effect. In both plantations, high shedding of leaves was significant only when the lowest values of heliophany and the highest values of relative humidity were recorded. Coincidentally, a high percentage of green leaf detachment was recorded with the characteristic symptomatology of the fungus Cylindrocladium sp. An accumulation of ABA, JA and SA hormones was detected in yerba mate plants with high shedding of leaves, which was associated with the attack of the necrotrophic fungus Cylindrocladium sp. With predisposing climatic conditions for the manifestation of Cylindrocladium, an early harvest would reduce the loss of green leaves. The differences found among plants Cylindrocladium attack could be due to a genetic condition. The JA pathway may be the most important line of defense activated by Cylindrocladium infection. A high accumulation of JA and ABA has been detected in plants with high leaf shedding that could suppress the SA signaling pathway responsible for SAR establishment.